2018
DOI: 10.3390/en11020445
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble-Based Data Assimilation in Reservoir Characterization: A Review

Abstract: This paper presents a review of ensemble-based data assimilation for strongly nonlinear problems on the characterization of heterogeneous reservoirs with different production histories. It concentrates on ensemble Kalman filter (EnKF) and ensemble smoother (ES) as representative frameworks, discusses their pros and cons, and investigates recent progress to overcome their drawbacks. The typical weaknesses of ensemble-based methods are non-Gaussian parameters, improper prior ensembles and finite population size.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 74 publications
(128 reference statements)
0
4
0
Order By: Relevance
“…1 because they do not consider the geological meaning of reservoir parameters. It has been reported that this problem can be solved by techniques such as localization in many studies (Watanabe and Datta-Gupta 2012;Luo et al 2018;Jung et al 2018). Since this research is not a study to improve the ensemble-based method, only the standard ensemble-based methods are used as a comparison of the proposed method.…”
Section: Characterization Of Channel Connectivitymentioning
confidence: 99%
“…1 because they do not consider the geological meaning of reservoir parameters. It has been reported that this problem can be solved by techniques such as localization in many studies (Watanabe and Datta-Gupta 2012;Luo et al 2018;Jung et al 2018). Since this research is not a study to improve the ensemble-based method, only the standard ensemble-based methods are used as a comparison of the proposed method.…”
Section: Characterization Of Channel Connectivitymentioning
confidence: 99%
“…As for the batch estimation techniques, it is possible to estimate the terms with lower corresponding variances assuming the fact that not only the signal values up to the current time is used but also the future values of the signals can provide information to lower the estimation error variance. EKF-smoother and its computationally efficient version Rauch-Tung-Striebel (RTS) smoother is often preferred to construct the state trajectories and parameter estimations [20,21]. Additionally, there are also Bayesian smoothers that use different approaches where not only the value of the state vector at a given instant is estimated but also the whole state trajectory is determined using dynamical programming techniques [22].…”
Section: Introductionmentioning
confidence: 99%
“…Roughly, these methods for assisted history matching can be divided into two categories [7]: the data assimilation approaches (such as Ensemble Kalman Filter and Ensemble Smoother) and the optimization approaches (such as gradient, evolutionary or data-driven-based algorithms). Ensemble Kalman Filter (EnKF) and Ensemble Smoother (ES) are representative methods for data assimilation [8]. For example, EnKF is a sequential Monte Carlo approximation of the Kalman filter where the correlation between reservoir parameters and observed production data can be estimated from the ensemble with the uncertainty of estimation [9].…”
Section: Introductionmentioning
confidence: 99%
“…To address the limitations, various EnKF extensions were developed through localization, ensemble design scheme and clustering methods, etc. [8,10]. In contrast to the iterative process of EnKF, ES could simultaneously assimilate all the production data in a global update, which is much faster than EnKF [11].…”
Section: Introductionmentioning
confidence: 99%